Fresno Merced Counties Legal Services Staff Farewell Potluck for Nancy Currier - Watkins, Howard::::::::: (1981)
Carolyn Phillips, David Cisneros holding "We Will Miss You" cake, Nancy Currier blowing out candles, ?, Cindy Calvert